2020
DOI: 10.3389/fmed.2020.00022
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Pregnancies Complicated With Preeclampsia or HELLP Syndrome

Abstract: Acute kidney injury that occurs during pregnancy or in the post-partum period (PR-AKI) is a serious obstetric complication with risk of significant associated maternal and fetal morbidity and mortality. Recent data indicates that the incidence of PR-AKI is increasing, although accurate calculation is limited by the lack of a uniform diagnostic criteria that is validated in pregnancy. Hypertensive and thrombotic microangiopathic disorders of pregnancy have been identified as major contributors to the burden of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
10

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 113 publications
2
46
1
10
Order By: Relevance
“…Endothelium injury-induced thrombotic microangiopathy also induced tubular ischemia, sequentially aggravated by postpartum hemorrhage and ischemia-reperfusion. It is worth noting that some studies have shown that the occurrence of TMA with ATN might increase the severity of CKD [48,49] as also demonstrated by the development CKD in our study. Since the renal prognosis of TMA combined with ATN induced by severe postpartum hemorrhage is relatively poor we recommend the use of early renal biopsy to con rm the disease and thus limit disease progression.…”
Section: Discussionsupporting
confidence: 76%
“…Endothelium injury-induced thrombotic microangiopathy also induced tubular ischemia, sequentially aggravated by postpartum hemorrhage and ischemia-reperfusion. It is worth noting that some studies have shown that the occurrence of TMA with ATN might increase the severity of CKD [48,49] as also demonstrated by the development CKD in our study. Since the renal prognosis of TMA combined with ATN induced by severe postpartum hemorrhage is relatively poor we recommend the use of early renal biopsy to con rm the disease and thus limit disease progression.…”
Section: Discussionsupporting
confidence: 76%
“…La mayoría de las características clínicas son atribuibles al tono vascular irregular, el vasoespasmo extenso y la deficiencia en la coagulación (1). Se dice que no se ha logrado dilucidar por completo el mecanismo fisiopatológico (13,14), sin embargo, existen varias teorías con respecto a las complicaciones hipertensivas durante el embarazo, en la más aceptada, se hace referencia a la implantación insuficiente de las células del citotrofoblasto (4), lo que provoca que las arterias espirales se mantengan estrechas y fibróticas, generando una disminución en el flujo placentario al feto (4,5). Esta hipoxia placentaria genera la liberación de diferentes factores placentarios, entre los que se encuentran el factor de crecimiento vascular soluble receptor-1, el factor de crecimiento endotelial vascular y el factor de crecimiento placentario (5,9).…”
Section: Fisiopatologíaunclassified
“…-Hígado graso agudo del embarazo: Típicamente se presenta en el tercer trimestre, en algunos casos también en el periodo posparto(13), entre 1-7,000-15,000 casos por año(13), sin sintomatología específica, muchas pacientes se presentan con hipertensión sin embargo, esta característica es más frecuente en el síndrome de HELLP. Es de suma importancia hacer un correcto diagnóstico ya que, esta es una emergencia obstétrica que puede progresar rápidamente al desarrollo de falla renal, encefalopatía, hipoglicemia severa (17) y falla hepática fulminante (13).…”
Section: Diagnóstico Diferencialunclassified
See 1 more Smart Citation
“…ve hem anne hem de fetüs için yüksek bir risk oluşturabilmektedir(28). Şiddetli vakalarda HT'ye ek olarak karaciğer fonksiyonunda bozulma ve trombositopeni (HELLP sendromu) gelişebilir(29). Küçükgöz ve arkadaşları (30) erken preeklampsinin, geç dönem preeklampsiden daha yüksek PU düzeyi ile ilişkili olduğunu göstermiştir.…”
unclassified